THE INFLUENCE OF TRUST, COMMITMENT AND COMMUNICATION ON CUSTOMER RETENTION FOR SUPERMI PRODUCTS IN LHOKSEUMAWE CITY - Wirdatul Ahya; Heriyana; Adnan; Hamdiah (RADJA PUBLIKA, 2024)
This problem has become a problem in marketing activities which are currently intensively competing in the food industry. and resulting in increasingly strong business competition. Many companies compete to attract consumer attention from competitors with the aim of maintaining and increasing company sales. Many companies compete with each other to win the first position in the position of Best Brand in the Food Industry. One food product that currently has quite good marketing potential is instant noodles. Indofood is one of the Instant Noodle market segments which has been known since 1968 with its product Supermie. However, the development of instant noodles increased and competition was very sharp, causing Supermi products to experience a decline, especially after the launch of Mie Sedap by the Wings Group. The aim of this research is to analyze and determine the influence of trust, commitment and communication on customer retention in Lhokseumawe City. This type of research is quantitative research with a consumer population in Lhokseumawe City. Respondents totaled 120 people, taken using purposive sampling technique. The data source comes from primary data obtained through distributing questionnaires. The data analysis techniques used are descriptive analysis methods and multiple linear regression analysis, classical assumption tests, instrument tests (validity and reliability), hypothesis tests and coefficients of determination as well as correlation tests and analyzed with the help of the SPSS version 26 application program. The results of the research show that in general Simultaneous trust and commitment have a positive and significant effect on customer retention for Supermie products in Lhokseumawe City. Meanwhile, partially the communication variable does not have a significant influence on customer retention. However, the variables of trust and commitment have a significant influence on customer retention for supermie products in Lhokseumawe City.